Pengaruh Paparan Radiasi Gelombang Elektromagnetik Wi-Fi 4G terhadap Berat Epididimis dan Morfologi Sperma Tikus Jantan Wistar - Meily Nirnasari (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to determine how the effect of Wi-Fi4G electromagnetic radiation exposure on epidedemic testis weight and sperm quality in Wistar male rats (Rattus Norvegicus). The research method used in the study is an experimental research method with posttest control group design. The results of data analysis were performed with the One Way Anova test, after being given exposure to 4G Wi-Fi electromagnetic radiation radiation showed significantly different mean, reduced epididymal weight, sperm morphology value (p = 0,000) with alpha value of 0.05 (p <Î±) compared with the control group. Conclusion, exposure to Wi-Fi4G electromagnetic wave radiation can reduce the epididymic weight and sperm morphology in male wistar rats. Keywords: Epididymis, Sperm Morphology, 4G Wi-Fi